2011
DOI: 10.1007/s00445-011-0535-3
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between collapse structures, hydrothermal systems, and magma intrusions: the case of the central area of Piton de la Fournaise volcano

Abstract: International audienceWe explore the possible relationships between a structural heterogeneity, the hydrothermal system, and the intrusive activity at Piton de la Fournaise volcano. Geological and geophysical data show that as the result of repeated collapses (the last one in 2007), a cylinder of faulted, fractured, and crumbled rocks must exist between the surface and the top of a magma reservoir at about sea level. This structure constitutes a major geological heterogeneity. An obvious spatial correlation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 82 publications
4
43
0
Order By: Relevance
“…On the uppermost part of the terminal cone, only signs of superficial fluid circulations along vertical discontinuities are visible. The hydrothermal system suggested by Lénat et al (2012), from a combination of geological and geophysical data, is confined deeper in the faulted and crumbled rock cylinder below the summit, as attested to by geo-electrical studies. From 300 m depth to the limited depth of investigation (∼1,000 m), Lénat et al (2000) observed an electrical conductor below the summit interpreted as the altered hydrothermal zone (resistivity values<20 Ωm below ∼500 m depth and <250 Ωm from ∼500 m up to ∼300 m depth), whereas the overburden (now exposed in the outcrops) is composed of resistive layers, interpreted as a water-sparse region (1,000 to 3,000 Ωm and>8,000 Ωm for the shallowest 100 m).…”
Section: Hydrothermal System Of the Piton De La Fournaise Volcanomentioning
confidence: 80%
See 1 more Smart Citation
“…On the uppermost part of the terminal cone, only signs of superficial fluid circulations along vertical discontinuities are visible. The hydrothermal system suggested by Lénat et al (2012), from a combination of geological and geophysical data, is confined deeper in the faulted and crumbled rock cylinder below the summit, as attested to by geo-electrical studies. From 300 m depth to the limited depth of investigation (∼1,000 m), Lénat et al (2000) observed an electrical conductor below the summit interpreted as the altered hydrothermal zone (resistivity values<20 Ωm below ∼500 m depth and <250 Ωm from ∼500 m up to ∼300 m depth), whereas the overburden (now exposed in the outcrops) is composed of resistive layers, interpreted as a water-sparse region (1,000 to 3,000 Ωm and>8,000 Ωm for the shallowest 100 m).…”
Section: Hydrothermal System Of the Piton De La Fournaise Volcanomentioning
confidence: 80%
“…As proposed by Lénat et al (2012), the hydrothermal system may play a role in the development of magma injections and volcanic instabilities and thus in the constructive and destructive phases of basaltic shields. During the most recent Piton de la Fournaise caldera collapses (notably in 2007), and as observed during the Miyakejima caldera collapse in 2000, no major explosive, phreatic or phreatomagmatic, activity and thus no strong magma-water interaction seemed to occur.…”
Section: Impact Of Summit Collapses On the Evolution Of Basaltic Shieldsmentioning
confidence: 99%
“…According to this hypothesis, possible seasonality can be proposed for the Piton de la Fournaise activity, linked to the annual hydrological cycle. Moreover, the inflation/deflation evolution of the volcano edifice could also be affected by the shallow hydrothermal system (Lénat et al, 2011), which could also play a role in the evolution of the stress field.…”
Section: Influence Of the Rainy Seasonmentioning
confidence: 99%
“…Long-lived hotspot eruptions at Kilauea, Hawai'i (e.g., Poland et al, 2008) and Piton de la Fournaise, Réunion (e.g., Peltier et al, 2010), as well as repeated episodes of intrusion in the Galapagos (e.g., Bagnardi et al, 2013) dominate the small number of systems worldwide where multiple cycles of eruption have been observed geodetically (although this also includes non-hotpot volcanoes such as Okmok, Aleutians, Biggs et al, 2010a). As well as cycles of pre-eruptive uplift followed by co-eruptive subsidence, such long-lived eruptions have also provided evidence for endogenous growth, change in intrusion location in response to varying stress fields (e.g., Bagnardi et al, 2013) and cycles of feedback related to topographic structures (e.g., Jónsson, 2009;Lénat et al, 2012).…”
Section: Insights From Global Insar Volcano Deformation Measurementsmentioning
confidence: 99%